To franchise or not to franchise? Is Culver's ButterBurger a "better burger"? - Williams, Jaime, (SAGE Knowledge. Cases., 2018)
Culver's, a made-to-order fast food restaurant based in Wisconsin, has differentiated itself from the competition through its specialized menu and focus on customer service. This case shows how Culver's has applied strategic management tactics to grow a local business to locations in half of the United States. The case examines the operating strategy of the business, including product, market entry timing, and target market, and then outlines the branding approach used to expand the restaurant in multiple regions throughout the United States. Finally, it summarizes where Culver's currently stands as a company and where they are heading in the future.